"The Effectiveness of Team Teaching Supported by Blended Learning in Developing Selected Teaching Skills among Third-Year Students at the College of Physical Education and Sport Sciences" (Al-Muthanna Journal of Sport Education Sciences, 2026)
This research aimed to identify the effectiveness of team-based teaching enhanced with blended learning in developing certain teaching skills among third-year students at the College of Physical Education and Sports Sciences, University of Mosul.The researchers used an experimental design with two equivalent groups (experimental and control) using pre- and post-tests, the research sample consisted of 40 students, divided into two groups of 20. The experimental group studied using a team-based teaching strategy enhanced by blended learning, while the control group studied using the standard method. A teaching skills assessment form was used as the research instrument, covering six main areas: planning the learning situation, interpersonal and educational relationships, classroom management, the objectives of the physical education lesson, subject-matter knowledge, and lesson implementation.The statistical methods used included: the arithmetic mean, standard deviation, simple and multiple correlation coefficient tests, paired samples t-test, unpaired samples t-test, and chi-square test.The results showed statistically significant differences between the pre-test and post-test scores for both the experimental and control groups, although the differences were more pronounced and favored the experimental group. The results also revealed a significant advantage for the experimental group over the control group in the post-tests across all teaching skills dimensions.The researchers concluded that team-based teaching enhanced with blended learning is more effective than the traditional method in developing teaching skills among third-stage students. The researchers recommended the necessity of adopting this strategy in teaching the subject of teaching methods, organizing training courses for faculty members, and conducting subsequent studies on other academic stages and disciplines.